2016
DOI: 10.1152/ajpcell.00067.2016
|View full text |Cite
|
Sign up to set email alerts
|

Furthering the debate on the role of interstitial cells of Cajal in enteric inhibitory neuromuscular neurotransmission

Abstract: The gut, a muscular organ, performs a critical role in transporting ingested contents, yet it is also controlled to periodically stop transport to maximize digestion and toxin detection. The complex intraluminal composition and rheology challenge the mechanistic requirements of inhibitory neuromuscular neurotransmission. The interstitial cells of Cajal (ICCs)-generated slow wave may tune the promiscuous luminal chemical environment, which prepares the smooth muscle membrane potential for a depolarizing or hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…However, the prolonged release of nitric oxide prevents the restoration of membrane potential to baseline and aims to maintain the hyperpolarization. This is manifested as the slow inhibitory junction potential (sIJP), unambiguously recorded by several investigators across decades (Figure 1; Bennett et al, 1966; Atanasova et al, 1972; Smith et al, 1990; Hirst et al, 2004; Allego et al, 2008; Chaudhury et al, 2011, 2012; Chaudhury, 2016a). Following the paradigm-shifting demonstration of ATP as a neurotransmitter using gut tissues (Burnstock et al, 1970), there was a gap of several decades in which the VNUT could not be identified within the synaptic vesicles.…”
Section: Enteric Inhibitory Smooth Muscle Neurotransmission Involves mentioning
confidence: 76%
See 4 more Smart Citations
“…However, the prolonged release of nitric oxide prevents the restoration of membrane potential to baseline and aims to maintain the hyperpolarization. This is manifested as the slow inhibitory junction potential (sIJP), unambiguously recorded by several investigators across decades (Figure 1; Bennett et al, 1966; Atanasova et al, 1972; Smith et al, 1990; Hirst et al, 2004; Allego et al, 2008; Chaudhury et al, 2011, 2012; Chaudhury, 2016a). Following the paradigm-shifting demonstration of ATP as a neurotransmitter using gut tissues (Burnstock et al, 1970), there was a gap of several decades in which the VNUT could not be identified within the synaptic vesicles.…”
Section: Enteric Inhibitory Smooth Muscle Neurotransmission Involves mentioning
confidence: 76%
“…Evoked enteric inhibitory neuromuscular neurotransmission involves the sequential release of purines (most importantly, ATP) and the gas nitric oxide (NO), synthesized by neuronal nitric oxide synthase (nNOS) at the membranes of nerve terminals (Chaudhury et al, 2011, 2012; Chaudhury, 2014, 2015a, 2016a,b). While ATP is stored in the vesicles of the nerve terminals, NO is synthesized de novo (Chaudhury, 2016a). The released ATP during evoked neurotransmission hyperpolarizes the smooth muscle membrane (Chaudhury, 2016a).…”
Section: Enteric Inhibitory Smooth Muscle Neurotransmission Involves mentioning
confidence: 99%
See 3 more Smart Citations